Application of STEM-based LKPD on Reaction Rate Material to Improve Students' Critical Thinking Ability - Rahmah, Aulia; Sugiharti, Gulmah (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
The use of STEM-based LKPD can improve students' critical thinking skills. In this study, non-test instruments such as validation questionnaires and test instruments with 5 aspects of critical thinking were used. This study aims to 1) measure the validity of the developed LKPD; 2) determine students' responses to the developed LKPD; 3) determine the improvement of students' critical thinking skills; 4) determine whether students' critical thinking skills on the use of STEM-based LKPD developed better than without using STEM-based LKPD. Data collection techniques through BSNP questionnaire, student response questionnaire and N-Gain test for critical thinking improvement and right-sided t test. The samples were 70 students of class XI F1B and XI F2D who were randomly selected. Based on the material and media expert validators, it shows that 94.34% of the material experts and 87.5% of the developed LKPD media experts have a very high interpretation and the level of validity is "Very valid". While 87.27% of student responses were rated "Very good" for use in learning the topic of reaction rates. The N-Gain test results showed the gain of the experimental class taught using STEM-based LKPD was 0.81 while the control class gain without STEM-based LKPD was 0.71. The t-test showed tcount=3.276> table=1.667. Thus it can be concluded that the use of STEM-based LKPD is very good in lectures on the topic of reaction rate.